Comparative Analysis of Nutritional, Textural, and Sensory Attributes of Butter Crab and Normal Female Mud Crab (Scylla paramamosain): Insights for Market Positioning and Consumer Preference - Baojia Chen; Mingfei Feng; Kang Fang; Kun Wu; Hai Yang; Shaojian Chen; Haoji Guo; Shuangli Hao; Xiaobo Wen (Foods)
In recent years, the butter crab (BC), a distinctive phenotypic variant of the female mud crab Scylla paramamosain, has garnered increasing market attention due to its perceived superior nutritional and sensory attributes. This study conducted a comprehensive comparative analysis of the nutritional composition, textural properties, and sensory characteristics of BC and normal female mud crab (NFMC). Results showed that the muscle and hepatopancreas of BC contained significantly higher lipid contents (0.77 and 22.14 g/100 g wet weight) and elevated levels of DHA + EPA (18.36% and 12.86% of total fatty acids), which contributed to its characteristic orange–yellow coloration, as reflected by colorimetric values (L* × a* × b* = 30.20 × 4.38 × 16.15). Sensory evaluation revealed that BC exhibited enhanced umami taste and aroma in both muscle and hepatopancreas, corresponding to higher concentrations of umami amino acids (0.75 and 1.95 mg/g wet weight) and aldehydes (35.06% and 34.37% of total volatiles), respectively. In addition, 80% of panelists preferred BC based on visual appearance, indicating its strong consumer appeal. Overall, this study advances our understanding of the biochemical and sensory profiles of BC and NFMC and provides important insights for market positioning of BC in the premium seafood sector.